CD8+ T-Cell Epitope Variations Suggest a Potential Antigen HLA-A2 Binding Deficiency for Spike Protein of SARS-CoV-2 - Qiu, Congling; Xiao, Chanchan; Wang, Zhigang; Zhu, Guodong; Mao, Lipeng; Chen, Xiongfei; Gao, Lijuan; Deng, Jieping; Su, Jun; Su, Huanxing; Fang, Evandro Fei; Zhang, Zhang-Jin; et al. (Frontiers in Immunology, 2022)
We identified SARS-CoV-2 specific antigen epitopes by HLA-A2 binding affinity and ability to activate T cell. As the pandemic continues, variations in virus strains have been found in many countries. In this study, we directly assess the immune response to SARS-CoV-2 epitope variants. We first predicted potential HLA-A2 restricted CD8+ T cell epitopes of SARS-CoV-2. Using the T2 cell model, HLA-A2 restricted T cell epitopes were screened for their binding affinity and ability to activate T cell. Subsequently, we examined the identified epitope variations and analyzed their impact on immune response. Here we identified specific HLA-A2 restricted T cell epitopes in the spike protein of SARS-CoV-2. Seven epitope peptides were confirmed to bind with HLA-A2 and potentially be presented by antigen presenting cells to induce host immune responses. Tetramers containing these peptides could interact with specific CD8+ T cells from convalescent COVID-19 patients, and one dominant epitope (n-Sp1) was defined. These epitopes could activate and generate epitope-specific T cells in vitro, and those activated T cells showed cytolytic activity toward target cells. Meanwhile, n-Sp1 epitope variant 5L>F significantly decreased the proportion of specific T cell activation; n-Sp1 epitope 8L>V variant showed significantly reduced binding to HLA-A2 and decreased proportion of n-Sp1-specific CD8+ T cell, which potentially contributes to the immune escape of SARS-CoV-2. Our data indicate that the variation of a dominant epitope will cause the deficiency of HLA-A2 binding and T cell activation, which subsequently requires the formation of a new CD8+ T cell immune response in COVID-19 patients.